Islamisation of political thought courses at IIUM - Isahak, Aldila (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
This article examines and analyses as to how Political Thought courses i.e. Political Thought I and Political Thought II, at the Department of Political Science of IIUM, are Islamized. The rationalization as to why selected thinkers from Classical Greek till Postmodernism was also done. These thinkers include both from the West and the Muslim world.